2014
DOI: 10.1063/1.4896475
|View full text |Cite
|
Sign up to set email alerts
|

A new variable temperature solution-solid interface scanning tunneling microscope

Abstract: We present a new solution-solid (SS) interface scanning tunneling microscope design that enables imaging at high temperatures with low thermal drift and with volatile solvents. In this new design, distinct from the conventional designs, the entire microscope is surrounded in a controlled-temperature and controlled-atmosphere chamber. This allows users to take measurements at high temperatures while minimizing thermal drift. By incorporating an open solution reservoir in the chamber, solvent evaporation from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Molecular self-assembly from solution onto surfaces is widely embraced as a strategy for creating adlayers with desirable electronic, photonic, and chemical properties. 10 Throughout the last two centuries, understanding chemical reactions has included the ability to measure kinetics (rates of reaction) and to measure and/or predict the thermodynamically stable product. If we are to develop a rational method for predicting the surface structures that yield optimal processes, we must understand the fundamentals about how adlayers are formed and react at the solution-solid interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular self-assembly from solution onto surfaces is widely embraced as a strategy for creating adlayers with desirable electronic, photonic, and chemical properties. 10 Throughout the last two centuries, understanding chemical reactions has included the ability to measure kinetics (rates of reaction) and to measure and/or predict the thermodynamically stable product. If we are to develop a rational method for predicting the surface structures that yield optimal processes, we must understand the fundamentals about how adlayers are formed and react at the solution-solid interface.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Very recently an alternative configuration wherein the entire STM exists in a controlled environment has been demonstrated. 10 Throughout the last two centuries, understanding chemical reactions has included the ability to measure kinetics (rates of reaction) and to measure and/or predict the thermodynamically stable product. This competition between kinetics and thermodynamics is a fundamental conflict that underlies all of chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…STM has the potential to track single molecules on a time scale of milliseconds to hours and allows one to study the dynamics of monolayer formation on surfaces. As advances in STM continue, new doors open for investigating and understanding various surface phenomena under previously inaccessible conditions. For example, Jahanbekam et al showed that by enclosing the whole STM body in a controlled chamber one can perform temperature dependent studies on volatile solvents such as toluene (up to at least 75 °C) …”
Section: Introductionmentioning
confidence: 99%
“…Generally, they were flattened and smoothed with a Gaussian 1 filter. High-resolution STM images were corrected for thermal drift as described in a previous study …”
Section: Experimental Sectionmentioning
confidence: 99%